2021
DOI: 10.1177/1940161221991550
|View full text |Cite
|
Sign up to set email alerts
|

Online Incidental Exposure to News Can Minimize Interest-Based Political Knowledge Gaps: Evidence from Two U.S. Elections

Abstract: Concerns persist over the potential for the fragmented media environment to promote motivation-based political knowledge gaps between those who are interested in politics and those who are not. Yet, there is also evidence that the Internet can provide opportunities for individuals to incidentally encounter and learn from news, which may decrease these knowledge gaps. The current study tests this possibility using two, two-wave panel surveys of adults in the United States conducted during the 2012 and 2016 pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…First, that a single, brief exposure to a party cue detectably influenced opinions 3 days later speaks to the potential power of party cues in shaping public opinion. It is likely that even people who do not follow politics closely are occasionally exposed to party cues on various issues; our results imply these exposures may well exert meaningful influence, that is, that persists beyond a day or two (see also Weeks, Lane, and Hahn 2021).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…First, that a single, brief exposure to a party cue detectably influenced opinions 3 days later speaks to the potential power of party cues in shaping public opinion. It is likely that even people who do not follow politics closely are occasionally exposed to party cues on various issues; our results imply these exposures may well exert meaningful influence, that is, that persists beyond a day or two (see also Weeks, Lane, and Hahn 2021).…”
Section: Discussionmentioning
confidence: 65%
“…First, that a single, brief exposure to a party cue detectably influenced opinions 3 days later speaks to the potential power of party cues in shaping public opinion. It is likely that even people who do not follow politics closely are occasionally exposed to party cues on various issues; our results imply these exposures may well exert meaningful influence, that is, that persists beyond a day or two (see also Weeks, Lane, and Hahn 2021). Furthermore, party cues are easily disseminated – and increasingly so – to large numbers of people via social and partisan media, meaning that short-term persistence may be “topped-up” regularly, and with little effort on the part of consumers.…”
Section: Discussionmentioning
confidence: 68%
“…With the rise of social media, studies have investigated whether news use on social media can lead to objective knowledge gains as it did on traditional media (Cho et al, 2009;Eveland, 2001;Sotirovic & McLeod, 2001). While some studies found positive (Anspach et al, 2019;Weeks et al, 2021) and others found negative effects (Van Aelst et al, 2022), a recent meta-study detected no effect for social media use on objective political knowledge (Amsalem & Zoizner, 2022).…”
Section: Social Media and Objective Political Knowledgementioning
confidence: 99%
“…In fact, many users report encountering politics online by chance, such as when going online for trivia or romance (Wojcieszak & Mutz, 2009) or connecting with friends and family on social media (Valeriani & Vaccari, 2016). These incidental exposures to politicswhether in televised infotainment (Andersen, 2019;Baek & Wojcieszak, 2009;Baum, 2003;Baum & Jamison, 2006;Moy, Xenos, & Hess, 2005) or online (Feezell, 2018;Heiss & Matthes, 2019;Kwak et al, 2020;Weeks, Lane, & Hahn, 2022) are cross-sectionally and -to a lesser extent -causally related to news use, political knowledge, participation, and political discussion, among other outcomes (Nanz & Matthes, 2022).…”
Section: News News Avoidance Incidental Exposurementioning
confidence: 99%